The Specific Features of the Pathogenesis and Correction of Critical Conditions in Obstetric Care - Yu. S. Podolsky (Общая реаниматология)
Objective: to analyze the research areas determining the pathogenesis and correction of critical conditions in obstetric care in the past 15 years on the basis of the dissertations made at the V. A. Negovsky Research Institute of General Reanimatology. Subjects and methods. Nine hundred and twenty-nine pregnant women, parturients, and puerperas were examined; the latter were allocated to comparison groups in terms of age, weight, comorbidity, performed intensive therapy and underwent both retrospective and prospective analysis from 1981 to 2010. The comparison group comprised 44 nonobstetric patients while examining multiple organ dysfunction (MOD) in the purperas. The latter with massive blood loss were separately identified when evaluating the impaired oxygen status in patients with systemic inflammatory response syndrome and MOD. According to the pathology and indicators under study, the puerperas with MOD were examined in a few steps (2 to 7). Water sectoral disorders were detected in three steps: on days 1, 3, and 5; these were identified in four steps in case of eclamptic coma (EC), regional anesthesia, and impaired oxygen status. Results. The findings are suggestive of significant impairments in central hemodynamics (CHD) in the severe forms of gestosis, which are caused by reductions in cardiac index and circulating blood volume, the basis for these is hypovolemia. Dyshidrosis appears as an increased extracellular sector mainly due to interstitial hyperhydration. The low values of arterial blood oxygen, its delivery and uptake, oxygen extract coefficient and the high value of oxygen debt (OD) confirmed blood shunting or circulatory centralization, which was indicative of visceral hypoxia. Determination of the level of cerebral blood flow (CBF) in puerperas with coma showed its diminution due to reduced blood flow in the cortical structures. Regional anesthesia in complicated pregnancy and delivery stabilized CHD, dropped the level of proteinuria, and failed to have a negative impact on the fetus and to cause extragenital manifestations. Conclusion. The proposed algorithms for treating critical conditions in obstetric care contributed to the normalization of CHD parameters, the recovery of water sectoral balance and immune status, resulted in lower mortality rates in MOD, and could increase CBF and minimize OD, reducing the duration of comatous state in EC and the length of stay in intensive care units.